Profile of Sexual Assault Cases Registered in the Department of Forensic Medicine, Rajshahi Medical College (TAJ: Journal of Teachers Association, 2009)
A cross sectional study was conducted among 291 victims of sexual assault cases examined at the department of Forensic Medicine, Rajshahi Medical College from February to June, 2004 in order to see the profiles of the sexual assault cases. In this study the mean age of the victims was 17.78 years. Out of 291 victims 3 individuals were male. The incidence of sexual assault was more frequent among the individuals aged from 14 to 18 years. The study should that 77.7% victims were unmarried. 80% individuals of sexual assault were inhabitants of rural areas and the rest of the victims were of urban areas. The study revealed that 88 (30.2%) had the signs of violence on their body. In finding out of the physical development the study presented that 86.9% victims had developed breast while 8.9% had not. Out of 288 female victims 84.72% female had old tear of hymen while 30 (10.41%) had recent hymenal tear. 1.4% victims of sexual assault showed presence of sperm in pathological examination.   doi: 10.3329/taj.v18i2.3174 TAJ 2005; 18(2):